2005
DOI: 10.1007/s00267-003-0107-1
|View full text |Cite
|
Sign up to set email alerts
|

Illegal Logging Activities in Turkey

Abstract: Global forest ecosystems are under the threat of illegal logging. In this article, illegal logging activities and the principal causes of such violations are discussed in view of the available data and case studies from the Turkish forestry sector. A brief discussion of the importance of illegal logging within a global context, along with a description of Turkish forestry and deforestation activities, is provided. Underlying causes of illegal logging are discussed, and some solutions are recommended. It is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Lochner and Moretti (2004) studied the effect of education on criminal activity and their results suggested that when the increasing education level decreases the crime levels. Gunes and Elvan (2005) investigated the logging activities in Turkey and concluded that the underlying causes of logging are related to the economic, political, and cultural structures of Turkish society. Similarly, in a study by Gençay and Mercimek (2019), a survey was conducted in Kastamonu province of Turkey to investigate the impact of laws on forest crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Lochner and Moretti (2004) studied the effect of education on criminal activity and their results suggested that when the increasing education level decreases the crime levels. Gunes and Elvan (2005) investigated the logging activities in Turkey and concluded that the underlying causes of logging are related to the economic, political, and cultural structures of Turkish society. Similarly, in a study by Gençay and Mercimek (2019), a survey was conducted in Kastamonu province of Turkey to investigate the impact of laws on forest crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Limited legal timber supplies combined with the demand for this product created by end users encourage villagers, wholesalers and local officials to participate in illegal logging and trafficking activities (McElwee 2004, Gunes & Elvan 2005, Sikor & To 2011. In 1993, the Vietnamese government promulgated a logging ban in protected areas known as 'special use forests', and in 2014, it prohibited the cutting of trees from 70% of natural forests (IUCN 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The failure of the logging bans requires forest managers to find additional approaches to restrict the demand for illegal timber from natural forests. Since socioeconomic factors may be linked to the consumption patterns of timber from natural forests (Gunes & Elvan 2005, De Medeiros et al 2012, one possible approach is to develop interventions based on the socioeconomic profiles of consumers. However, not enough is known about the relationships between socioeconomic factors and the consumption patterns of timber at the household level in Vietnam and more generally (De Medeiros et al 2012, Ramos et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…3 Considering the importance of this ecosystem several countries consider the cutting of vegetation and plants as illegal. [4][5][6][7] An example is what happens in Chile, where the cut of native vegetation might be considered as an environmental damage. In Chile the environmental damage is regulated by the law No.…”
Section: Introductionmentioning
confidence: 99%